Framing the development and directions of business sustainability efforts. Issue 4 (1st August 2016) - Høgevold, Nils M.; Svensson, Göran
Abstract : Purpose: To frame the development and directions of business sustainability efforts. Design/methodology/approach: A qualitative study was undertaken with respect to a convenience sample of reputable companies in Norway, which have implemented significant business sustainability efforts within their organisations, their business networks, the marketplace and in the society, beyond the level of mere compliance. Findings: Different directions are associated with the development of corporate efforts in connection with business sustainability. Business sustainability efforts are not static, but dynamic and based upon continuous flexibility to changes and adaptations over time. Research limitations/implications: The current study highlights the need for further research into the development and directions of corporate efforts in connection with business sustainability in the marketplace and society. A key suggestion for further research is to further explore the existence of other directions. Practical implications: The directions reported, provide a framework to assess the development or the status of companies' business sustainability efforts in the marketplace and society. Corporate efforts in connection with business sustainability develop over time as experiences are gained and personal impressions move the identified directions forward. Originality/value: This study contributes to seven interconnected directions of corporate efforts in connection with business sustainability that are both relevant and potentially fruitful to both scholars and practitioners.